Társadalmi és egyházi reformtörekvések a Csanádi egyházmegyében 1848/49-ben - Zakar, Péter (Közép-Európai Közlemények, 2011)
In 1848 the Diocese of Csanád covered the whole territory of Csanád, Torontál, Temes, and Krassó counties along with the military frontiers, and some parts of Csongrád county also belonged to it at that time. The number of Catholics was about to 448320, whose spiritual care belonged to 188 parishes. The centre of the bishopric, Temesvár was both nationally and religiously diverse, and a great number of its priests supported the civil movements and the democratic reforms in the church government. Their main point was abolishing celibacy, which they thought to be crucial in solving many other problems of church. The Points of Csanád are the expression of their aims. They wanted a democratic church government, open church courts and open procedures. Another point was abolishing the patron law, and they stated that priesthood oughtn’t to be indelible. They claimed that divorce matters should be taken over by secular courts. They also wanted to disband the monastic orders, and to wear secular clothes with the exception of altar-service. They urged the reform of boarding-houses, emphasised the importance of teaching in Hungarian, and wanted a fair share of duties between chaplains and parish-priests. Another claim was state salary for priests and old-age-pension. Among others they wanted to reform the holidays, the breviary, the fast, and the services. They were planning to discuss these reforms on a national synod. The majority of these priests supported not only the religious but the social reforms as well, and many of them took an active part in the war of independence in 1848–1849.